Analysis Of Attitudes Towards Local Food Products Of Rejang Culture In Central Bengkulu Regency - Sri Ekanengsih; Herri Fariadi; Rika Dwi Yulihartika (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2023)
Local food products receive less attention by the people in Pondok Kelapa District and without realizing it the position of local food products is increasingly marginalized and rarely found at this time. This is marked by the growing development of modern culinary sellers and modern retailers such as Indomaret and Alfamart in all corners of Bengkulu Province. The purpose of this study is to identify the types of local food products of Rejang culture, to find out the attitude of the people towards the local food products of Rejang culture, to find out the level of community’s knowledge of the local food products of Rejang culture in Central Bengkulu Regency. The research method used is a qualitative method using domain analysis and descriptive analysis. Data collected through questionnaires, tabulated using Microsoft Excel to give a score according to the system applied. The results showed that there were 18 identified types of local food for Rejang tribe which were classified into 3 categories, namely side dishes (4 types), pelampun food (snacks) (8 types) and drinks (6 types). The community's attitude towards the local food of Rejang tribe in Central Bengkulu Regency is categorized as very good or very like it. The community's knowledge of the local food of Rejang tribe in Central Bengkulu Regency, on average, is in the medium or good category.